Iron oxide nanoparticle coating of organic polymer-based monolithic columns for phosphopeptide enrichment - Krenkova, Jana; Foret, Frantisek (Journal of separation science, 2011)
A new monolithic capillary column with an iron oxide nanoparticle coating has been developed for selective and efficient enrichment of phosphopeptides. Iron oxide nanoparticles were prepared by a co-precipitation method and stabilized by citrate ions. A stable coating of nanoparticles was obtained via multivalent electrostatic interactions of citrate ions on the surface of iron oxide nanoparticles with a quaternary amine functionalized poly(glycidyl methacrylate-co-ethylene dimethacrylate) monolith. A high dynamic binding capacity of 86 μmol/mL column volume was measured with an adenosine-5'-triphosphate. Performance of the monolithic column was demonstrated with the efficient and selective enrichment of phosphopeptides from peptide mixtures of α-casein and β-casein digests and their MALDI/MS characterization in off-line mode.
Keywords: Chromatography, Liquid; Phosphopeptides; Ferric Compounds; Polymers; chromatografie kapalinová; Monolithic column; kaseiny; nanočástice; polymery; Nanoparticles; Caseins; fosfopeptidy; železité sloučeniny; Enrichment; Iron oxide nanoparticles